Confucian family ideal and same-sex marriage: A feminist Confucian perspective - TAN, Sor-hoon (Institutional Knowledge at Singapore Management University, 2024)
This article engages the views of PRC Confucian scholars who responded to the United States Supreme Court Justice Anthony Kennedy's citing of Confucius in his majority opinion on same-sex marriage in 2015. It questions their separation of tolerance for homosexuality from legalization of same-sex marriage and argue that tolerance is not enough. The arguments in the mainland Confucian discourse about same-sex marriage highlights the historical and persistent entanglement of Confucianism with patriarchy. Instead of reviving traditional patriarchal society, further entrenching and increasing gender inequality, contemporary Confucianism could shape its own unique modern society that aspires to (and hopefully one day achieving) gender equality together with sexual inclusivity by deconstructing the patriarchal Confucian family and reconstructing a different Confucian family ideal. Accepting same-sex marriage would lend weight to the latter, and there are Confucian reasons for legalizing same-sex marriage and recognizing its ethical value.